Persepsi Nasabah Tentang Kepatuhan Syariah Dan Good Corporate Governance Terhadap Loyalitas Nasabah BNI Syariah Kantor Cabang Surabaya - Oktaviani, Atika; Rachmawati, Lucky (Universitas Negeri Surabaya, 2019)
The aim of the research is to test effect of sharia compliance and good corporate governance towards loyalty of customers of BNI Syariah Branch Office Surabaya. This research was condacted with an associative quantitative approach. Number of sampel that used in this research is 100 responden from customer BNI Syariah Branch Office Surabaya. The analysis in this study used multiple linear regression. The result of this research show that simultaneously sharia compliance and good corporate governance has a positive effect to loyalty of customers. Based on patial test show that variable sharia compliance not significantly effected to loyalty of customers and variable good corporate governance significantly effected to loyalty of customers.